2023
DOI: 10.24018/ejfood.2023.5.1.609
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Natural Honey for Cane Sugar (Sucrose) Retards Microbial Growth Independent of Water Activity During Storage of Tomato Jam

Abstract: Today, there are several attempts to make nutritious food products low in glycemic carbohydrates as this can partly help in solving the ever-growing numbers of type 2 diabetes and obesity. We thus made two types of jam, one using conventional sucrose with a high glycemic index and the other using honey which is regarded as a low glycemic index carbohydrate.  Honey jam had comparable physical properties with sucrose jam. The total soluble solid (Brix) was significantly lower in honey jam than in sucrose jam (p=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The relationship between Brix and honey quality was assessed when coding Brix values and low Brix honey was coded 1 because it contains less sugar (Kapira et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between Brix and honey quality was assessed when coding Brix values and low Brix honey was coded 1 because it contains less sugar (Kapira et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Conti (2000) reported that honey moisture and sugar content show a signi cant correlation and that abnormal values can be taken as an indicator of honey adulteration. In one study, honey jam (consisting of 625 grams of honey instead of sugar) was found to have a signi cantly lower Brix value than sucrose jam (p < 0.05), suggesting that honey jam contains less sugar (Kapira et al 2023). When the studies are examined, it is understood that the Brix level of honey can provide information about the sugar content of honey.…”
Section: Introductionmentioning
confidence: 99%